2021
DOI: 10.1136/bmjopen-2021-049738
|View full text |Cite
|
Sign up to set email alerts
|

Experience of living with type 1 diabetes in a low-income country: a qualitative study from Liberia

Abstract: IntroductionWhile epidemiological data for type 1 diabetes (T1D) in low/middle-income countries, and particularly low-income countries (LICs) including Liberia is lacking, prevalence in LICs is thought to be increasing. T1D care in LICs is often impacted by challenges in diagnosis and management. These challenges, including misdiagnosis and access to insulin, can affect T1D outcomes and frequency of severe complications. Despite the severe nature of T1D and growing burden in sub-Saharan Africa, little is curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Qualitative interviews conducted at this site found that challenges to diabetes management include high levels of poverty and food insecurity, low levels of literacy and numeracy, and high temperatures causing insulin damage, increasing the risk of diabetic ketoacidosis hospitalisation. 12 Patients travel long distances to the clinic monthly for consultations and insulin refills. All health services, medications, insulin and diabetes necessities (ie, glucometer, test strips, lancets and syringes) are provided to patients at no cost.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative interviews conducted at this site found that challenges to diabetes management include high levels of poverty and food insecurity, low levels of literacy and numeracy, and high temperatures causing insulin damage, increasing the risk of diabetic ketoacidosis hospitalisation. 12 Patients travel long distances to the clinic monthly for consultations and insulin refills. All health services, medications, insulin and diabetes necessities (ie, glucometer, test strips, lancets and syringes) are provided to patients at no cost.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Frequency of SMBG and missed insulin doses were identified as priority self-management behaviours by local providers and in the qualitative assessment of T1D care in rural Liberia. 12 DSME mentors will collect data on core NCD providers’ utilisation of DSME, the use of the patient assessment tool, and frequency of referrals for interdisciplinary care by directly observing patient interactions and completing a mentoring checklist. Similar checklists have been effective in promoting retention of learning and improved quality of care for PLWD in rural Rwanda.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology follows that used in our previous qualitative study in Liberia and utilizes similar interview tools. 13…”
Section: Data Collectionmentioning
confidence: 99%
“…Our team previously conducted a qualitative study on T1D care at PIH-supported PEN-Plus clinics in Liberia and here we describe a similar study in Malawi to further build on this body of evidence. 13 In this study, we examine the impact of living with T1D, knowledge of the disease and self-management, and facilitators and barriers to T1D care at two clinics in Neno.…”
Section: Introductionmentioning
confidence: 99%